PEMIKIRAN HARUN NASUTION (RELIGIUS-RASIONAL) TENTANG PENDIDIKAN ISLAM DAN RELEVANSINYA DENGAN DUNIA PENDIDIKAN ISLAM KONTEMPORER - Rosita Dongoran; Maragustam Siregar (Jurnal Shaf, 2025)
This article aims to analyze Harun Nasution's thoughts regarding religious-rational Islamic education and its relevance to the world of contemporary Islamic education. This research uses a type of library research (Library Research) where the researcher tries to collect library data, read, take notes, and process various information about Harun Nasution's thoughts regarding education and its relevance to the modern world, especially in Indonesia, through various related sources. The results of this research are explaining Harun Nasution's thoughts regarding Rational Islam with the aim of deepening the teachings of the Islamic religion through the use of rational religious thinking so that he is able to adapt to current developments and be able to solve problems, as well as explaining Harun Nasution's thoughts which emphasize the importance of moral aspects to be instilled in students who aims to shape student behavior and morals that are in line with Islamic teachings